Potential strategies to manage bronze beetle (Eucolaspsis sp) in organic apple orchards - Rogers, D.J.; Cole, L.M.; Fraser, T.M.; Walker, J.T.S. (New Zealand Plant Protection, 2007)
Bronze beetle (Eucolaspsis sp Coleoptera Chrysomelidae) threatens the viability of New Zealands organic pipfruit industry Small plot cultivation trials were conducted during spring to target immature beetles in the soil in a 25 m strip under apple trees A single cultivation treatment in October prevented 56 to 81 of the beetle population from emerging When plots were tilled every second week from October to December 79 to 95 failed to emerge The pattern and timing of bronze beetle emergence during 2006 was consistent between the four trial orchards and with the 2005 season A survey of 20 orchards during November 2006 was unable to link beetle damage levels with management practices and the physical environment New strategies to manage bronze beetle larvae are discussed